The Effect of Baby Massage on the Sleep Quality of Babies Aged 3-6 Months - Yanti, Yuli; Irmaya, Hanny; Wandila, Dika (Global Health Science Group, 2024)
Good quality sleep is very important for everyone in improving physical and mental health. Because sound sleep is very important for growth, especially for babies. During sleep, the baby's brain growth reaches its peak. (Motors & Europe, 2016). Baby massage therapy is a method used to reduce and help sleep pattern disorders in babies aged 3-6 months. This type of research is descriptive using a case study approach model. The sample was two respondents who were given baby massage therapy for seven days. The parents of both respondents stated that they were quite familiar with baby massage but did not know about the theory of baby massage, had already done baby massage but did not know how to do baby massage. However, after being educated and taught, the parents of the two respondents were able to absorb the knowledge provided, so they understood the theory of baby massage and were able to practice how to do baby massage properly and correctly. The results of the research on the two respondents after being given baby massage were very effective and had particular benefits for improving the quality of sleep in children to overcome sleep pattern disorders and provide a sense of comfort to babies. From the results of this research, it was found that baby massage therapy is very effective in overcoming sleep pattern disorders to improve the quality of sleep in babies after application within seven days.